Cleaner production in electroplating industry: A case study - K. V, Liew,; Agamuthu, P. (Malaysian Journal of Science, 2004)
Electroplating plants in Malaysia are mostly categorized as small and medium scale industries (SMIs) and there are more than 300 in number mostly situated in the Kiang Valley [5]. This case study was conducted at a SMI plant — Metal Polishing Sendirian Berhad situated at Bukit Kemuning, Shah Alam. The plant started operation in 1998 and currently employs 33 staff. This plant was selected as a model plant by Standards and Industrial Research Institute of Malaysia (SIRIM) and Japan International Cooperation Agency (JICA) to devise cleaner production (CP) options. Through implementation of CP the plant is experiencing the benefits whereby operation cost was reduced by approximately RM 3200 per month. There was a decrease in the cost of electricity usage from RM 49,800 to RM 44,800 thus giving a reduction of 10% on the energy bill. A recycling policy was implemented whereby alkaline rinse water was reused and chrome rinsing water were 100% recycled. Chrome rinse or sludge was also reduced from 14m3 to 4m3. These caused the usage of city water supply to reduce from 979m3 to 576m3 (a reduction of 41%) with a saving of approximately RM 193 per month. Two personnel were redundant and were removed as the direct result of CP implementation. This gave a saving of RM 1200 per month. The CP usage resulted in increased efficiency, cost saving and the plant was able to achieve the ISO 14001 in the year 2002.